Visual functions in phenylketonuria: evaluating the dopamine and long-chain polyunsaturated fatty acids depletion hypotheses - Gramer, Gwendolyn; Förl, Birgit; Springer, Christina; Weimer, Petra; Haege, Gisela; Mackensen, Friederike; Müller, Edith; Völcker, Hans Eberhard; Hoffmann, Georg F.; Lindner, Martin; Krastel, Hermann; Burgard, Peter (Molecular genetics and metabolism, 2013)
Background: In phenylketonuria presymptomatic treatment following newborn screening prevents severe mental and physical impairment. The reasons for subtle impairments of cerebral functions despite early treatment remain unclear. We assessed a broad spectrum of visual functions in early-treated patients with phenylketonuria and evaluated two hypotheses—the dopamine and the long-chain polyunsaturated fatty acids (LCPUFAs) depletion hypotheses. Methods: Contrast sensitivity, colour vision, electroretinography, frequency doubling technology campimetry (FDT), and their relation with blood phenylalanine and docosahexaenoic acid levels were assessed in 36 patients with phenylketonuria and 18 age-matched healthy controls. Results: Contrast sensitivity was significantly lower and total error scores in colour vision significantly higher in patients than controls. Electroretinography results differed significantly between patients and controls. We found a trend for the effect of phenylalanine-levels on contrast sensitivity and a significant effect on colour vision/FDT results. Docosahexaenoic acid levels in erythrocytes were not associated with visual functions. Conclusion: This is the first evaluation of visual functions in phenylketonuria using a comprehensive ophthalmological test battery. We found no evidence supporting the long-chain polyunsaturated fatty acids depletion hypothesis. However, the effect of phenylalanine-levels on visual functions suggests that imbalance between phenylalanine and tyrosine may affect retinal dopamine levels in phenylketonuria. This is supported by the similar patterns of visual functions in patients with phenylketonuria observed in our study and patients with Parkinson's disease.
Gesehen am 26.04.2018